Struktura literacka mowy świętego Szczepana (Dz 7, 2-53) - Szymik, Stefan (The Biblical Annals, 2017)
St. Stephen’s speech (Ac. 7, 2-53) is among the more difficult texts in the Acts; this can be gathered from the many disagreements among commentators. One of the disputed points concerns its literary composition, its internal literary structure. Most writers have not attached much importance to the problem, judging the chronology to constitute a sufficient criterion for the division of the speech. Representatives of the formgeschichte school, who have concentrated on the study of the deep structure of the tact (diachronic analysis), neglected the question of its literary composition. Yet current research shows ever more forcefully that Stephen’s speech needs to be studied also from the viewpoint of its literary and theological unity (synchronic analysis). This is so because the speech has a logical and purposely designed internal structure, a literary structure. It is the aim of this article to discover that internal structure. Apart from chronological and thematic criteria we have taken into account also the linguistic and stylistic characteristics of the speech. Our study reveals that the first major part of the speech coven the earliest history of Israel, from Abraham until the death of the last of Jacob’s sons (w. 2-16). The next part concentrates solely on the events of Moses’ life (w. 17-36); a noteworthy point about this part is its emphatic conclusion, where Moses is proclaimed to be the liberator of Israel (w. 35-36). The third part of the speech is more varied in content, but the theme of the people and their attitude towards Moses and towards religious cult is dominant (w. 37-50). Particularly remarkable is the beginning of this part, which is introduced by the promise of the coming of another prophet like Moses (v. 37), a point that has a variety of important justifications. The speech doses with violent invective against the Jews (w. 51-53). This final invective stands in contrast to the other three parts of the speech; at the same time, however, there is an interdependence here, based on shared themes and motifs (w. 2-50, 51-53).